The delay and fairness study of a centralised EPON DBA algorithm - Radzi N.A.M.; Din N.M.; Sadon S.K.; Al-Mansoori M.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Ethernet Passive Optical Network (EPON) is one of the most promising technologies for FTTX deployed by service providers at the access network. Dynamic Bandwidth Allocation (DBA) for the upstream traffic can help optimize the network bandwidth utilization. This paper discusses a centralized DBA called as Universal DBA (UDBA) algorithm that supports quality of service (QoS) of the upstream traffic. UDBA algorithm is compared with other DBA algorithm to prove its advantages. It shows that UDBA algorithm improves upon expedited forwarding, assured forwarding and best effort delay on average 62.2%, 36.3%, and 23.1% respectively. The fairness index of UDBA algorithm is improved as high as 5.4%. © 2014 IEEE.